Successful Transition From Primary to Secondary School for Students With Autism Spectrum Disorder: A Systematic Literature Review. Issue 3 (3rd July 2019) - Richter, Mechthild; Popa-Roch, Maria; Clément, Céline
ABSTRACT: The transition from primary to secondary school is a sensitive phase in the life of a child, especially within vulnerable groups such as children with autism spectrum disorder (ASD). ASD characteristics, such as the refusal to change or social interaction difficulties, present challenges to the transition not only for the students themselves, but also for their parents and the teachers involved in the transition process. For the literature review, 16 studies focusing on the primary-secondary transition for children with ASD were selected. Based on criteria existing in the literature for students without special needs, the selected articles were analyzed for identifying factors that enable a successful transition for children with ASD. The literature review confirms these criteria to a major extent, but also modifies and adds new criteria, which involve all main stakeholders and the transition preparation. Both are of crucial importance for students with ASD. These new criteria enable the evaluation of the primary-secondary transition of children with ASD and provide starting points for further research in order to better understand and improve the situation of students with ASD in mainstream education settings.